Instilling Utilization of Fermentation of Corn Cob Waste for Animal Feed by Mesa Pau Farmers Group in Ihing Village - Wandi Abbas*; Sutrisno Sutrisno; Lilis Ambarwati (Riwayat: Educational Journal of History and Humanities, 2023)
One of the activities carried out is to take advantage of the potential in the village so that it can be a solution for villagers, namely the use of corncob waste to become animal feed with economic value. The method used in this activity is through direct training to the Mesa Pau Farmers' group, namely the socialization, processing, and utilization of corncob-fermented feed products. The aim of implementing this program is to provide a medium for managing the potential of Ihing village, namely by conducting training for the Mesa Pau Farmers Group so that they can develop the potential of corncob waste to become animal feed. Implementation of this activity includes; the production process starting from grinding/chopping, fermentation, and use, and the packaging process for packaging and marketing which is carried out conventionally and through e-commerce. The results of this activity are to produce animal feed from fermented weevil waste which can later be used for the personal needs of village breeders and sold to other areas, especially in the Polewali Mandar district.